Stressors and coping strategies of elite para snowsport athletes - Heritage, P. D.; Cotterill, S. T. (AECC University College, 2022)
With institutional ethics granted five elite, male para-snowsport athletes (mean age 34.6 ± 7.8 years), with elite snowsport experience of two to five years and amputation of one or both legs, were interviewed using semi-structured interviews. Data were analysed adopting a reflexive thematic analysis approach.